Role of interleukin-36 in kidney disease - Bi-xia Yang; Hua Zhou; Min Yang (Editorial Department of Journal of Clinical Nephrology, 2023)
As an important member of IL-1 family, interleukin 36 (IL-36) is a key regulator of inflammation. Its proinflammatory agonists are composed of IL-36α, IL-36β and IL-36γ while its antagonists include IL-36Ra and IL-38. And co-receptor of IL-36 subfamily is IL-36 receptor (IL-36R). An imbalance of IL-36 agonists and antagonists may lead to the development of skin diseases, intestinal diseases, lung diseases and tumors. In recent years, many studies have confirmed that IL-36 is correlated closely with the occurrence and development of kidney diseases. This review focused on the structure, biological function, regulatory mechanism and role of IL-36 in kidney disease